Akame ga kill! Zero. 8 - Takahiro, 1981- (Yen Press, 2018)
"Akame's physical recovery after her harrowing experience with the Oarburghs is relatively quick, but her mind is still racked with confusion. The suffering of the people, not to mention the suffering of her sister, is undeniable. But rash action on a team where even perceived betrayal is dealt with swiftly and harshly would be dangerous. Akame must resolve her intentions soon. The enemies of Squad "A" are growing-and even now, they are gathering together to take out their common foe..."-- Page [4] of cover.